ANALYTICAL MODELING OF A LARGE LOCAL AREA NETWORK - PART I: INTERNET TRAFFIC CHARACTERIZATION - Luhanga, Mathew L.; Amos, Cuthbert E. B. M (Tanzania Journal of Engineering and Technology, 2018)
The goal of both IP network operators and the end users is to get the highest performance from the system for a given cost. This makes Performance a key criterion in the design, procurement, and use of computer and communication systems. In order to address problems associated with performance degradation of operational communications systems, over the last decade, traffic engineering techniques have emerged in an attempt to optimize communication systems ' performance and ensure more efficient use of their resources. One of these techniques is analytical modeling. Analytic performance models are an excellent tool for quickly evaluating the performance of operational or new systems. They are also well suited to comparing the performance of several alternative designs. However, analytical models can only be developed once detailed knowledge of characteristics of traffic carried by a network is available. In Part I of this paper, traffic characterization of traffic carried by the largest Local Area Network (LAN) in Tanzania, University of Dar es Salaam Network (UDSMNET) is carried out. In Part II of this paper, an analytical model based on the Discrete Time Markov Modulated Poisson Process is proposed and validated for performance analysis of IP networks.